Análise sensorial de óleos essenciais de eucalipto: um Estudo de Caso - MONTEIRO, Heloise Leal (2020)
Essential oils are highly volatile substances that can be extracted through plants, flowers, roots, fruits and other materials found in nature. This work aimed to compare olfactory and tactile sensations through the sensory analysis of eucalyptus oil using hedonic scale between a commercial and a non-commercial sample, and thus to conclude if both have the same aromatic effects. The sample of the commercial oil was acquired through the purchase of a multinational company that sells essential oils. The non-commercial essential oil was extracted from the eucalyptus leaves, collected in the municipality of Marituba-PA, which was obtained through the process of hydro-distillation of 50g of leaves. The analyses of the chemical composition of the two samples were performed by GC-MS technique. The sensory tests were performed using as reference the hedonic scale with a group of individuals. The gross yield was 2.2%. The chemical composition presented 1.8-cineol as the majority component for the two oil samples, 15.06% and 27.8%, respectively for non-commercial and commercial. In general, the sensory tests did not present significant differences, but the main comments about the non-commercial sample were those made about the aroma of this rustic woody type, and the "texture" parameter, which was evaluated as more oily than the commercial sample, but this factor did not interfere in the positive evaluations regarding the non-commercial oil.